Development and in vitro evaluation of micronized sustained release matrix tablet of carvedilol - Chatterjee, Bappaditya; Pal, Tapan (International Journal of Pharmaceutical Sciences and Research (IJPSR), 2010)
Carvedilol, a non selective β blocking drug under the biopharmaceutical classification system (BCS) class II, is widely used in the treatment of hypertension. Solubility of this drug is very low which affects in low dissolution rate and in turn affect the bioavailability of this drug following oral administration. The micronization of drug is one of the technological procedures to improve the dissolution rate. The purpose of the present study is to design a sustained release matrix tablet containing micronized carvedilol phosphate. Phospahte salt of carvedilol possesses better aqueous solubility than it’s free base. Hydroxy propyl substituted β cyclodextrin and poly ethylene oxide are used as release modifying polymer to develop the matrix tablet. The comparative in vitro evaluation between the developed micronized sustained release and non-micronized sustained release matrix tablet of carvedilol are done. A significant increase in in vitro drug release rate is observed in case of the micronized product over the non micronized one. The sustained release matrix tablet of micronized carvedilol may be used as a once daily formulation after relevant pharmacokinetic studies.